PENGARUH KONTEN VLOG MEDIA SOSIAL TIKTOK TERHADAP PEMBENTUKAN SIKAP IMITATIF GENERASI Z (Studi Korelasional pada Generasi Z (Gen Z) Pengguna Aplikasi TikTok #adayinmylife di Kota Bandung) - Rezaiva Humaira Tuffahaty, - (2023)
This research background is motivated by the rapid development of social media which makes it easier for Generation Z to access and imitate all activities displayed, especially in the TikTok application. The aims of this research is to analyze how much influence duration, frequency, and attention of the simultaneous on #adayinmylife vlog content on TikTok's social media on the formation of imitative attitudes of Generation Z in Bandung City. This study uses a correlational study method with a quantitative approach. The sampling technique in this study is purposive sampling with a total sample of 100 Generation Z respondents who follow the #adayinmylife vlog content or have watched #adayinmylife vlog content on TikTok. The sample was taken using a survey via Google Form. The results of the study show the following. First, there is an significant duration effect of 1,967 between #adayinmylife vlog content on social media TikTok on the formation of Gen Z imitative attitudes in the Bandung City. Second, there is an significant frequency effect of 0,183 between #adayinmylife vlog content on social media TikTok on the formation of Gen Z imitative attitudes in the Bandung City. Third, there is an significant attention effect of 4,016 between #adayinmylife vlog content on social media TikTok on the formation of Gen Z imitative attitudes in the Bandung City. Thus, it can be concluded that there is a simultaneous effect of duration, frequency, and attention on #adayinmylife vlog content on social media TikTok on the formation of imitative attitudes of Generation Z. Consequently, this study has direct implications for Generation Z related to the formation of imitative attitudes with the overall results showing the magnitude of the regression between the independent variable and the dependent variable is 74.9%.